Penilaian Guru Sebagai Alat untuk Meningkatkan Kualitas Layanan Pendidikan - Nadia Difka Silfiana; Siti Nur Asiyah; Tata Elyya Tadya Nenggar; Wulan Ramadhani; Lisa Virdinarti Putra (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2025)
Teacher performance appraisal plays a crucial role in improving the quality of education services. This study adopts a qualitative approach through literature analysis to examine the influence of teacher performance appraisal on professional development and service quality in schools. The analysis focuses on various models of teacher evaluation, including performance-based assessments, 360-degree feedback, and portfolio assessments, each offering different benefits and challenges. The findings show that well-structured evaluations contribute to teachers' reflective practices and enhance instructional quality when supported by clear standards, constructive feedback, and sufficient evaluator training. However, the implementation faces obstacles such as limited evaluator competence, technological constraints, resistance from teachers, and administrative burdens. Several case studies at primary and secondary levels illustrate the effectiveness of technology integration and systematic evaluation approaches, though disparities remain due to unequal infrastructure and varying stakeholder readiness. This paper recommends that future teacher assessment systems balance accountability with professional growth, emphasize formative and developmental feedback, and streamline processes to ensure sustainable and impactful implementation.